1998
DOI: 10.1002/(sici)1097-4636(199822)43:2<175::aid-jbm12>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Bruxing-type dental wear simulator for ranking of dental restorative materials

Abstract: An instrumented dental wear test simulator was developed to simulate jaw movement in the chewing process between two molar teeth. It simulated the natural impact with sliding masticatory action, known as bruxing (defined as the gnashing, grinding, or clenching of teeth) type of wear, in order to simulate a worst-case dental wear scenario. In vitro wear testing of dental restorative materials was performed. Impact and sliding wear were simulated on the machine, with water as the lubricant, on three metal alloys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…When adding 30% for safety reasons, FPDs need to show fracture forces of 250-300 N in anterior and 450-500 N in posterior areas (Kotioth et al 1997;Hidaka et al 1999). In artificial oral environments (DeLong & Douglas 1991;Teoh et al 1998), materials in new or somewhat risky application modes can be tested before conducting cost-intensive and time-consuming clinical trials. They can simulate various clinical parameters such as moisture and thermal or mechanical loading.…”
Section: Date: Accepted 3 December 2007mentioning
confidence: 99%
“…When adding 30% for safety reasons, FPDs need to show fracture forces of 250-300 N in anterior and 450-500 N in posterior areas (Kotioth et al 1997;Hidaka et al 1999). In artificial oral environments (DeLong & Douglas 1991;Teoh et al 1998), materials in new or somewhat risky application modes can be tested before conducting cost-intensive and time-consuming clinical trials. They can simulate various clinical parameters such as moisture and thermal or mechanical loading.…”
Section: Date: Accepted 3 December 2007mentioning
confidence: 99%
“…The stress applied through the cast chromium counterbody was higher than that found clinically (3·9-17·3 MPa) during mastication (Anderson, 1956) to allow for stresses generated during nocturnal parafunction which could be as high as 60% that of maximum clench when a person is awake (Clarke, Townsend & Carey, 1984). As the ranking of materials' performance on the wear simulator was consistent with published clinical ranking (Teoh et al, 1998), this simulator model was used to study the quantitative wear of posterior restoratives (Yap et al, 1999). Emphasis was placed on the restoratives as our primary objective and not the counterbody although cast chromium alloys have been shown to be abraded by some composites (Willems et al, 1992).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, fundamental in vitro wear tests are important for the study of the wear mechanisms, provision of data during material development and screening of materials prior to clinical trials. One of the latest in vitro wear tests developed for the study of wear mechanisms is the BIOMAT wear simulator (Teoh et al, 1998). This wear simulator was designed and made to duplicate as closely as possible the intra-oral movement of molar teeth during chewing.…”
Section: Introductionmentioning
confidence: 99%
“…T eoh et al . (5) showed that small changes in the construction of a specific wear machine can significantly influence the ranking order of resin composites and amalgam. This illustrates the difficulties of in vitro wear tests to accurately simulate the oral conditions, and the need to better understand wear mechanisms occurring in the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…To study clinical wear is time‐consuming and expensive. In vitro tests provide an accelerated screening of the clinical wear at relatively low cost under controlled, reproducible conditions (1–7). Ceramic materials have often been criticised for being too hard and causing abrasion of opposing teeth and restorations.…”
mentioning
confidence: 99%